Pelatihan Efektifitas Kolaborasi dan Manajemen Konflik Aktivis Gereja Kristen X, Yogyakarta - Sinaga, Nurtaty; Princen; Isaputra, Samuel Adiprasetya; Matahari, David; Meliyanti (Fakultas Psikologi Universitas Pancasila, 2024)
This collaboration and conflict management training activity aimed to enhance the capacity of activists from Gereja X, Yogyakarta in collaboration and conflict management. The methods employed in this training included discussions, question-and-answer sessions, and game simulations. The training participants consisted of 31 church activists who were actively engaged in church ministry duties. A follow-up to the training activity was conducted one month after the event, involving both activists who participated in the training and those who did not. The follow-up result indicated that activists who participated in the training demonstrated a higher average level of collaboration compared to those who did not attend the training. Thus, it can be concluded that this training effectively improved church activists capacity for collaboration and conflict management.